Hand-foot-mouth disease: diagnostic challenges in atypical presentations (Archives of Pediatrics of Uruguay, 2026)
Hand, foot, and mouth disease is a common reason for consultation across various medical specialties due to its wide range of clinical presentations, from typical to atypical forms. In most cases, the diagnosis is clinical, and no treatment is required, as the disease typically resolves spontaneously. To facilitate its management and diagnosis, we have conducted a comprehensive, up-to-date bibliographic review of the most common clinical features, with a particular emphasis on atypical forms that help in early suspicion and diagnosis, thus minimizing delays and diagnostic errors.
Keywords: Hand, Foot and Mouth Disease; Skin Diseases